Green Marketing and Ecotourism Model Development Concept - Joko Suhariyanto (Institute of Computer Science (IOCS), 2022)
Tourism can grow and develop well when it is supported by government policies that are oriented towards the development of a sustainable tourism industry. This article intends to demonstrate the relevance of green marketing for tourism, particularly nature-based tourism. At the same time, this study demonstrates the risk of overuse of strong ecological characters, such as ecotourism and nature tourism among others, when associated with low-quality environmental products. This study uses a qualitative approach with descriptive methods in analyzing the results of research on the concept of green marketing and ecotourism. The results show that with the increasing importance of the natural environment in tourism, environmental marketing should be used by considering the parameters of social responsibility and ethics